FORMULASI DAN UJI IRITASI KRIM M/A DARI EKSTRAK ETANOL BERAS HITAM (Oryza sativa L. indica) - Aina Fatkhil Haque; Dewi Winni Fauziah; Nelsie Sopya Dayanie (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2019)
Black rice (Oryza sativa L. Indica) contains antioxidants which function to reduce fine lines on the face so that it can help neutralize free radicals that cause aging on the skin. Research on black rice extract as an active substance was obtained by maceration method using ethanol solvent 70% and made O/W cream preparations varied with 3 formulas, namely 2%, 4%, and 8%. The physical properties of the cream were tested, namely organoleptic test, homogeneity test, pH test, dispersion test, viscosity test, cream type test, hedonic test, irritation test. The evaluation results of this study are that each concentration of black rice extract can affect the physical properties of O/W Cream